Multidisciplinary Approaches to Reducing Postoperative Pulmonary Complications in Abdominal Surgery Patients: A Prospective Observational Study - Ibraheem, Khalida; Hussain, Agha Sajjad; Rana, Muhammad Asim; Ahmed Awad, Ahmed Hossameldin; Siddiqui, Mujtaba Hasan; Hashmi, Mubashar Sultan (Biological and Clinical Sciences Research Journal, 2025)
Postoperative pulmonary complications (PPCs) are a major cause of postoperative morbidity, especially in abdominal surgeries. Multidisciplinary strategies have been shown to reduce the incidence of PPCs in high-risk surgical patients. This study evaluated the effectiveness of coordinated perioperative interventions involving physiotherapy, nursing care, and surgical practices in reducing PPCs in a Pakistani tertiary care hospital. Methods: This prospective observational study was conducted over six months from August 2024 to January 2025 in a tertiary care hospital in Pakistan. Eighty-six patients undergoing elective or emergency abdominal surgery under general anesthesia were enrolled. Interventions included preoperative respiratory physiotherapy, intraoperative positioning strategies, early postoperative mobilization, incentive spirometry, and standardized nursing protocols. Patients were monitored for seven days postoperatively for the development of PPCs. Data were analyzed using SPSS v26, with p < 0.05 considered statistically significant. Results: The overall incidence of PPCs was 26.7%, with atelectasis (12.8%) and pneumonia (8.1%) being the most common. Patients who received multidisciplinary interventions had significantly lower rates of PPCs than those who did not (p < 0.01). Preoperative physiotherapy, early mobilization, and use of incentive spirometry were strongly associated with reduced PPC incidence. Patients with PPCs had longer hospital stays (mean 11.6 ± 3.2 days vs. 6.3 ± 1.9 days; p < 0.001) and higher ICU admission rates (39.1% vs. 6.3%; p = 0.001). Conclusion: A multidisciplinary approach significantly reduces the incidence of postoperative pulmonary complications in abdominal surgery patients. Early physiotherapy, mobilization, and respiratory care should be integrated into routine perioperative protocols, especially in resource-limited settings like Pakistan.